KNOWLEDGE AND ATTITUDE REGARDING SYSTEMIC LUPUS ERYTHEMATOSUS AMONG THE POPULATION IN KINGDOM OF SAUDI ARABIA (CAHIERS MAGELLANES-NS, 2024)
Background: Systemic lupus erythematous is an autoimmune disease. It is characterized by systematic chronic inflammation, which sometimes can lead to multi-organ damage. The disease can occur in often unexpected flares, with uncertain low and high disease activity. It can affect the joints, skin, brain, lungs, kidneys, and blood vessels.Objective: This study aims to estimate the knowledge and attitude regarding systemic lupus erythematosus among the population in Kingdom of Saudi Arabia.Methodology: This study was conducted through using a descriptive (cross- sectional survey) among the Saudi population, both male and female population aged 15 to 45 was convenient sample chosen as study participants. The duration of our investigation is from 1st of November 2022 to the 1st of July 2024. Using the Raosoft calculator, A minimum sample size of 384 is expected, by using a 95% confidence level and 5% margin of error. The Statistical Package of Social Science Software was used for statistical analysis (SPSS) Program for data analysis.Results: The study included 498 participants, 81.9% of them were females and 18.1% were males. 40.4% aged 20- 30 years old. 2% of participants have been diagnosed with SLE while 30% know someone who is diagnosed with SLE. 9.8% of participants have good knowledge score, 52.8% have moderate knowledge, and 37.3% have poor knowledge. 49.2% of participants have positive attitude towards SLE while 50.8% have negative attitude. As for knowledge, 96.6% reported that SLE patients should follow up with the attending physician and adhere to the plan. 28.5% know symptoms associated with lupus erythematosus. As for symptoms, 34.7% reported joint pain, 25.9% reported itching, and 10.2% reported hematuria. 50.4% reported that SLE has some complications. 13.1% reported that SLE affect the fertility of men and women. 29.7% think that SLE can cause fetal deformities or recurrent miscarriages for the affected mother. 90% reported that it is important to spread knowledge about SLE. 34.1% reported that SLE is preventable. 51.2% reported that SLE is curable.Conclusion: In conclusion, the participants exhibited poor knowledge and attitude towards SLE in Saudi Arabia. Knowledge was only significantly associated with gender while attitude was associated with age and educational level.